Real-time and video-recorded pain assessment in beef cattle: clinical application and reliability in young, adult bulls undergoing surgical castration - Tomacheuski, Rubia Mitalli; de Oliveira, Alice Rodrigues; Trindade, Pedro Henrique Esteves [UNESP]; Lopez-Soriano, Magdiel; Merenda, Victoria Rocha; Luna, Stelio P. Loureiro [UNESP]; Pairis-Garcia, Monique D. (Springer Nature, 2024)
Bovine pain assessment relies on validated behavioral scales related to normal and pain-related behaviors. This study investigated the reliability and applicability of real-time and video-recorded pain assessment, and their agreement, in young, adult bulls undergoing surgical castration. Ten Nelore and nine Angus bulls underwent general anesthesia and surgical castration. Three-minute real-time observations and simultaneous videos were recorded at − 48 h (M0), before sedation, under fasting (M1), after surgery, 3 h after sternal recumbency (M2), after rescue analgesia (M3) and at 24 h (M4). Animals received morphine (after M2), dipyrone (after M3), and flunixin meglumine after surgical castration (M4). Two trained evaluators assessed real-time (n = 95) and video-recorded time-points (n = 95) using the Unesp-Botucatu Cattle Pain Scale (UCAPS). Both assessment methods inferred ‘very good’ reliability (≥ 0.81) with minimal bias, however, video-recorded assessment (4.33 ± 2.84) demonstrated slightly higher scores compared to real-time (3.08 ± 2.84). The results from this study suggest that UCAPS can be used in real-time or video-recorded to assess pain and guide analgesic therapy in cattle.